Capital Inflows and Domestic Investment in Sub-Saharan Africa: Evidence from Pooled Mean Group (PMG) Estimation Approach. (November 2016) - Adams, Samuel; Sakyi, Daniel; Opoku, Eric Evans Osei
The issue of whether capital inflows promote domestic investment has been of major concern especially in developing countries considering their massive dependence on these inflows. To this end, we make a case for 25 sub-Saharan African countries, using foreign direct investment and external debt as proxies for capital inflows, and the pooled mean group estimator over the period 1981–2010. The results reveal that foreign direct investment positively impacts domestic investment, but external debt has a negative impact on domestic investment in the long run. This implies that increase in foreign direct investment and/or reduction in external debt will promote domestic investment in sub-Saharan Africa. Therefore measures have to be put in place to attract more foreign direct investment and reduce the inflow of external debt in the region.